2020
DOI: 10.3390/w12082217
|View full text |Cite
|
Sign up to set email alerts
|

Development of Pedo-Transfer Functions for the Saturated Hydraulic Conductivity of Forest Soil in South Korea Considering Forest Stand and Site Characteristics

Abstract: The saturated hydraulic conductivity (Ks) is one of the most important soil properties for many hydrological simulation models. Especially in South Korea, analyzing the Ks of the forest soil is essential for understanding the water cycle throughout the country, because forests cover almost two-thirds of the whole country. However, few studies have focused on the forest soil in the temperate climate zone on a nationwide scale. In this study, 1456 forest soil samples were collected throughout South Korea and ped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…It is worth mentioning that the K S of the coniferous pure forest was generally lower than that of coniferous and broad-leaved mixed forest. Lim et al analyzed 1456 soil samples from South Korea and found that K S in the broad-leaved mixed forest was significantly higher than that in the coniferous pure forest, which coincides with the results of this study [32]. Firstly, the roots of broad-leaved tree species were more widely spread laterally and produced a large number of small root branches, resulting in more developed soil pores than in coniferous forests [33].…”
Section: Characteristics Of K S In Different Stand Types Of the Study...supporting
confidence: 88%
“…It is worth mentioning that the K S of the coniferous pure forest was generally lower than that of coniferous and broad-leaved mixed forest. Lim et al analyzed 1456 soil samples from South Korea and found that K S in the broad-leaved mixed forest was significantly higher than that in the coniferous pure forest, which coincides with the results of this study [32]. Firstly, the roots of broad-leaved tree species were more widely spread laterally and produced a large number of small root branches, resulting in more developed soil pores than in coniferous forests [33].…”
Section: Characteristics Of K S In Different Stand Types Of the Study...supporting
confidence: 88%
“…The Ks is one of the essential parameter in order to predict K. In this study, it was estimated using falling-head approach [22]. Soil bulk density affects the Ks [23]. The Ks of different b were calculated using Eq.…”
Section: Hydraulic Conductivity Curvementioning
confidence: 99%
“…Despite the method yielding a relatively quick and inexpensive determination of Ksat, PTFs often do not include the spatial and temporal variability of soil water movement related to land use, land cover, and vegetation [22][23][24][25]. Previous studies showed that the reliability of PTFs is often limited in regions with similar soil properties and land-use history [17,[24][25][26]. Lim et al [25] determined the usefulness of six PTFs for Ksat prediction in forested soil of South Korea and concluded that observed Ksat was 10 times larger than Ksat estimated by PTFs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that the reliability of PTFs is often limited in regions with similar soil properties and land-use history [17,[24][25][26]. Lim et al [25] determined the usefulness of six PTFs for Ksat prediction in forested soil of South Korea and concluded that observed Ksat was 10 times larger than Ksat estimated by PTFs. Similarly, Petryk et al [26] analyzed the predictive accuracy of 15 PTFs in highly eroded loess soil samples and suggested a need to develop PTFs using local soil data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation